Matrix Extension Study: Validation of Compact Dry YM for Enumeration of Yeast and Mold in Selected Foods. (27th November 2019) - Mizuochi, Shingo; Nelson, Maria
Abstract: Nissui Compact Dry YM was originally certified by the AOAC Research Institute Performance Tested Methods SM (PTM) program (PTM No. 100401) for enumeration of yeasts and molds in fruit products after 7 days of incubation. A matrix extension study, organized by Campden BRI (Chipping Campden, United Kingdom), was conducted to extend the method's claim to cooked deli turkey, fresh whole tomatoes, cheese (Wensleydale), sliced white bread, and mayonnaise. In addition, the method was evaluated at 3 and 7 days to validate the 3 day incubation period. Compact Dry YM is a ready-to-use dry media sheet, containing a cold-soluble gelling agent, selective agents, and chromogenic medium, which are rehydrated by adding 1 mL diluted sample. Yeasts and molds appear as blue colonies, while molds can also have a cottony appearance and the color may vary. Users can obtain total yeast and mold count following 3–7 days of incubation at 25 ± 1°C. Method comparison data for cooked deli turkey, fresh whole tomatoes, cheese (Wensleydale), sliced white bread, and mayonnaise were collected in a single-laboratory evaluation by Campden BRI. A multilaboratory study was conducted on orange juice with 10 laboratories participating including the organizing laboratory. Compact Dry YM was compared to ISO 21527-1:2008, Microbiology of food and animal feeding stuffs–Horizontal method for the enumeration of yeasts and molds – Part 1: Colony count technique in products with water activity greater than 0.95, the current standard at the time of this study. Each matrix was evaluated for total yeasts and molds at each contamination level (including an uncontaminated level). In the single-laboratory evaluation (cooked deli turkey, fresh whole tomatoes, cheese, sliced white bread, and mayonnaise), colony counts were logarithmically transformed, and then the data were analyzed at each level for repeatability (sr ), RSD of repeatability (RSDr ), and mean difference between methods with a 95% confidence interval (CI). A CI outside a range of (−0.5 to 0.5) on the log10 mean difference between methods was used as the criterion to establish a significant statistical difference. In the multilaboratory study on orange juice, after logarithmic transformation the data were analyzed for sr, RSDr, and mean difference with 95% CIs and also for reproducibility (sR ) and RSD of reproducibility (RSDR ). Regression analysis was performed on all matrixes and reported as r 2 . Results from Compact Dry YM at 3 and 7 days were compared separately to ISO 21527-1 and then to each other. In the single-laboratory evaluation, five contamination levels were tested. With the exception of cheese, there were few, if any, colonies recovered at the two lowest contamination levels. As a consequence, differences of a few colonies resulted in significant statistical differences indicated between Compact Dry YM (at both 3 and 7 days) and ISO 21527-1 for most of the foods at these levels. At the three higher contamination levels, statistical differences were seen between Compact Dry YM at 3 days and the ISO method for cooked deli turkey at the middle level, tomatoes at the two middle levels, sliced white bread at the two highest levels, and mayonnaise at the middle level. After 7 days, statistical differences remained between Compact Dry and ISO methods, based on the CIs, but mean differences between methods were <0.5 log10 CFU/g for all foods at the three highest contamination levels. When comparing results between Compact Dry YM at 3 and 7 days, statistical differences were indicated for tomatoes and sliced white bread, both in the second highest contamination level. Otherwise, differences between results at 3 and 7 days were small. The sr and RSDr values were similar for Compact Dry YM (both days) and ISO 21527-1, and r 2 values were ≥0.84 for all comparisons. In the multilaboratory study for orange juice, there were no statistical differences between methods across 11 data sets. Four contamination levels were tested, and at all levels mean differences between methods were <0.1 log10 CFU/mL, and CIs were smaller than (−0.05, 0.15), well within the acceptance criterion of (−0.5, 0.5). The sr, RSDr, sR, and RSDr were similar for each method, and r 2 was 1.0 in all comparisons. Results indicate that Compact Dry YM offers comparable results at 3 days to the ISO standard plating method at 5 days, in a space-saving, easy-to-use format.